2018
DOI: 10.1590/1983-1447.2018.2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Segurança do paciente na administração de medicamento intramuscular em pediatria: avaliação da prática de enfermagem

Abstract: OBJECTIVE To evaluate the nursing care regarding the intramuscular medication administration procedure in pediatrics. METHODS It was an observational and quantitative study performed in a pediatric hospital located in the city of Fortaleza, in Ceará, Brazil. The data collection was carried out through the observation of 327 intramuscular medication administration procedures. An observational checklist composed by 25 steps was used to collect data. The performance of the 25 steps of the checklist was divided as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
12

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 4 publications
0
6
0
12
Order By: Relevance
“…On an ongoing basis, researchers have revealed that health education cannot be limited to just activities that address the transmission of information, since the process of learning demands the construction of strategies in which the didactic and pedagogical aspects meet the cultural dimensions, psychosocial, economic, and political aspects of a given community ( 19 - 20 ) . In this sense, when planning health education actions, the researcher needs to recognize the context to detect the factors that may contribute or hinder its development, with the transmission of information being only part of the process ( 21 ) . The population needs to recognize the need for actions so that they are incorporated into their daily lives, in order to improve the public health scenario in Brazil ( 22 ) .…”
Section: Introductionmentioning
confidence: 99%
“…On an ongoing basis, researchers have revealed that health education cannot be limited to just activities that address the transmission of information, since the process of learning demands the construction of strategies in which the didactic and pedagogical aspects meet the cultural dimensions, psychosocial, economic, and political aspects of a given community ( 19 - 20 ) . In this sense, when planning health education actions, the researcher needs to recognize the context to detect the factors that may contribute or hinder its development, with the transmission of information being only part of the process ( 21 ) . The population needs to recognize the need for actions so that they are incorporated into their daily lives, in order to improve the public health scenario in Brazil ( 22 ) .…”
Section: Introductionmentioning
confidence: 99%
“…We also know that there are multiple challenging factors in the construction of good professional nursing practice [ 26 ], so the lack of time availability of nurses (pointed out by four participants) can indicate that nurses are overloaded with work, either due to the lack of human resources or due to the bureaucratic processes (records) inherent to nursing care, which can be a demotivating and impeding situation for the effective development of HE practice. Additionally, in a study the participants pointed out the difficulties observed in the performance of nurses in primary care, the work overload, and the problems of human resources [ 28 ]. In this sense, problems such as the lack of employees, the high number of users, or the exhaustion of work are often faced by health professionals [ 27 ], and have been frequently pointed out in nursing studies that aim to understand the lack of quality, adverse effects events, and professional dissatisfaction in health care [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study also highlighted the importance for the managers to support the inclusion and Rev Gaúcha Enferm. 2019;40(esp):e20180306 visibility of the accompanying persons and family members in the strategies to promote safety (15) .…”
Section: Discussionmentioning
confidence: 99%